Patent litigation settlement in Germany: Why parties settle during trial - Katrin Cremers; Paula Schliessler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
This paper looks at the decision to settle patent litigation in Germany from a new angle by focusing on detailed data on within-trial actions and motivations by plain-tiff, defendant and the courts. Using a new dataset covering about 80% of all patent litigation cases in Germany between 2000 and 2008 we estimate the likelihood of within-trial settlement. We find that the within-trial settlement decision is to some degree driven by the proceedings that change the pre-trial setting of the negotiations in terms of information and stakes and make previously refused settlement a new option. Additionally, firm-specific stakes as measured by the relation of the involved parties to the disputed patent as well as firm-specific strategies are found to affect the general willingness to settle after the filing of a court case. The results suggest that pre-trial failure of settlement negotiations can to some extent be offset by within-trial settlement through efforts made by court and involved parties, but that the disposition to settle is to a larger degree determined by firm-specific stakes and strategies in the case.
Keywords: O34; K41; 330; Patent; Patent Litigation; Settlement